Waste-free processing of cassava in the food industry and bioenergy - M. M. Zheplinska; V. P. Vasyliv; M. M. Mushtruk; N. M. Zubar; O. M. Martyniv (Regulatory Mechanisms in Biosystems, 2025)
The development and implementation of waste-free resource- and energy-saving technologies is the basis for increasing pr o duction efficiency, which will help produce a comprehensive solution to the problem of resource supply of the economy and environmental protection. The production of food products, in particular starch, from non-traditional raw materials is increasingly attracting the attention of both researchers and manufacturers, as the population becomes more aware of the impact of healthy nutrition. This article provides a detailed review of current research on the use of cassava ( Manihot esculenta) in the food and processing industries. During the literature review, the ability to use waste-free technology for cassava processing was cons i dered, namely, obtaining food starch and flour from this type of raw material. Cassava flour, and accordingly, products from it, are suitable for consumption by people suffering from gluten intolerance, as well as people who seek to eat healthy food. This raw material is also promising for obtaining food starch. Waste s generated in the agro-industrial complex make up a significant share in the field of bioenergy production, including their consumption in the production of ethanol and biofuels, which has been the focus of attention of many researchers over the past decade due to the depletion of fossil oil reserves. Biofuel production from cassava starch began at the end of the last century, and the use of cassava residues, such as peel, bagasse, stem, root and leaves, is currently being intensively studied by researchers to identify their potential in biofuel production. Analysis of the scientists' r e search showed that it is worth highlighting several main areas of work on the use of cassava for partial or complete replacement of wheat flour with cassava flour in the production of bakery products, the production of starch for the food industry, biodegrad a ble material for food packaging and the production of bioethanol. The data obtained contain practical value regarding the poss i bility of using cassava and its waste-free processing, which is a relevant issue today.